1997
DOI: 10.1200/jco.1997.15.6.2385
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of unknown primary site: treatment with 1-hour paclitaxel, carboplatin, and extended-schedule etoposide.

Abstract: The combination of paclitaxel, carboplatin, and extended-schedule etoposide is highly active and well tolerated in patients with carcinoma of unknown primary tumor site. Response rates and survival in this multicenter community-based trial compare favorably with all previously studied empiric regimens. In addition, this regimen is substantially less toxic and easier to administer than the cisplatin-based regimens previously used in this setting. If this level of efficacy is confirmed, this treatment should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(49 citation statements)
references
References 24 publications
4
41
0
4
Order By: Relevance
“…Thus, to obtain clinically meaningful results, randomisation and multicentricity are of major importance even in phase II trials. On the basis of several phase II studies, platinum/taxane combinations are widely used in patients with CUP, yielding response rates of about 30% and a median survival of 7 -11 months (Hainsworth et al, 1997;Briasoulis et al, 1998;Greco et al, 2002;Park et al, 2004;El-Rayes et al, 2005). Gemcitabine has also gained considerable attraction recently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, to obtain clinically meaningful results, randomisation and multicentricity are of major importance even in phase II trials. On the basis of several phase II studies, platinum/taxane combinations are widely used in patients with CUP, yielding response rates of about 30% and a median survival of 7 -11 months (Hainsworth et al, 1997;Briasoulis et al, 1998;Greco et al, 2002;Park et al, 2004;El-Rayes et al, 2005). Gemcitabine has also gained considerable attraction recently.…”
Section: Discussionmentioning
confidence: 99%
“…Platinum/taxane combinations are widely used in patients with CUP, yielding response rates of about 30% and a median survival of 9 -11 months in selected patients in large phase II studies (Hainsworth et al, 1997;Greco et al, 2002). Gemcitabine has shown efficacy in second-line treatment and has recently been incorporated in first-line regimen.…”
mentioning
confidence: 99%
“…25 Hopefully, these reports will be the first step toward new progress in the management of patients with CUPs. 12 ViAM 57 30 7 De Campos et al 13 VACy 40 8 4 Hainsworth et al 14 PECa 53 47 13 Lofts et al 15 FcC 44 27 4 Parnis et al 16 FcEpC 43 19 6 Greco et al 17 DC …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a number of investigators, including particularly Hainsworth and Greco [30,48,52,54,55], have reported results. More recent studies have evaluated the use of a taxane/carboplatin [53] regimen coupled with etoposide [54] or gemcitabine [55].…”
Section: David M Mintzer Mdmentioning
confidence: 99%